Kesantunan Berbahasa dalam Pembelajaran Bahasa Indonesia di SMA Bilingual - Rosinawati Dewi; Sarwiji Suwandi; Edy Tri Sulistyo (Balai Bahasa Provinsi Riau, 2019)
Politeness are two important things that cannot be separated in learning activities. The purpose of this research is to explain the adherence to the principles of politeness in learning Indonesian dan the scale of politeness used in Indonesian language learning. The subject of this research is the students of grade 2 Al Abidin Bilingual Boarding Senior High School, Surakarta. Research methodology is descriptive qualitative which aims to generate data based on existing phenomenon empirically and the result is what it is. Research data is speech in learning Indonesian at Al Abidin Bilingual Boarding Senior High School Surakarta. Data collection methods that used in this research were uninvolved conversation observation, note taking, and recording technique. Validity of data in this research used triangulation technique of data source and triangulation method. The results of this research indicate that the dominant principle of politeness in Indonesian language learning in SMA Al Abidin Bilingual Boarding School Surakarta is (1) maxim of wisdom, (2) social distance scale used by students with other students, (3) social status scale used by students with teacher, (4) relative position scale of speech in learning occurs in official situations using Indonesian when interact between students and teachers.